Research Brief #7: Agriculture, Food Security and Nutrition in Nepal: Taking Stock and Defining Priorities. - Shrestha, Sudeep.; Manohar, Swetha.; Klemm, Rolf. (Tufts University. Tisch Library., 2016)
This briefing details the proceedings of a 2-day Scientific Symposium in Kathmandu Nepal. It contains a list of all presenters and a summary of the research covered during the event. Keyword: CRSP, Research Brief, Priorities, Scientific Symposium.